Mechanical physical study of concrete substitutes with silica powder exposed in simulated aggressive environment (Gaceta Técnica, 2018)
The present research resulted in a standardized laboratory test for the evaluation of physical and mechanical properties in a simulated exposure environment by immersion in 3% NaCl solution. The physical and mechanical evaluation was performed on reinforced cylindrical specimens of 30 cm high and 15 cm in diameter, made of concrete with partial replacement of the cement by dose silica in 10% and 15% water cement ratio of 0,45 and 0,65 and design strength of 250 Kgf/cm². Settlement tests, porosity, capillary absorption and mechanical resistance were performed In a period of 5 months, the influence of the substitutions of silica dust in the concrete mixtures with respect to the standard mixtures was analyzed, obtaining an increase in the mechanical resistance with respect to the design, in the ratio a/c 0,45, for the a/c ratio 0,65 reached acceptable values for the substituted mixtures with respect to the mechanical strength compared with the design, as for the porosity and capillary absorption tests were not satisfactory for any relation to a/c probably due to lack of curing prior to exposure
Keywords: aggressive environment; substituted concrete; silica powder; porosity; compression resistance